Peran Kepala Desa Dalam Meningkatkan Kesejahteraan Masyarakat Di Desa Gonting Garoga Kecamatan Garoga Kabupaten Tapanuli Utara - Kristina Pasaribu; Abdul Kadir; Yurial Arief Lubis (Universitas Medan Area, 2023)
The purpose of this study was to describe the role of the village head in improving community welfare in Gonting Garoga Village, Garoga District North Tapanuli Regency. This study uses a qualitative approach, with data collection techniques through interviews, observation and documentation. The subjects of this study were the village head and village apparatus, the head of the BPD, and the community. The object studied was the role of the village head in improving community welfare by using indicators from the part that is determined from the four. The results of this study indicate that the role of the Village Head in improving community welfare is measured from the four indicators, three indicators can be categorized as not optimal either including Innovators (Renewal), Pioneers and Modernizers (Thinking Forward). Â These three indicators are still very far from being found in the Gonting Village Government. Garoga, however, there is one indicator that is quite optimal, namely the stabilizer, which is to create stability both in terms of security and order in the midst of the Gonting Garoga community. The inhibiting factors include human resources, both the village head, officials and also the Gonting Garoga community themselves, people who are less interested in change.Â